Characterization of the histidine quinase protein CbrA and the role of the CbrX in P. putida KT2442 - Monteagudo Cascales, Elizabet; Santero, Eduardo; Canosa, Inés (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2016)
Motivation: The g-proteobacteria Pseudomonas, is present in a wide ecological niches due to metabolic, physiological and genetic versatility. It bears a very high number of regulatory systems that may allow them to adapt to many environmental conditions. Within this genus, P. putida KT2440 serves as a model microorganism of biotechnological interest. One of these regulatory two-components systems, unique in the pseudomonads, is CbrAB where CbrA is a histidine kinase sensor protein and CbrB a transcriptional activator of σN-dependent promoter, many involved in the assimilation of different C sources [1,3]. In this project, we will characterise the role of CbrA in the reception of the environmental signal to activate Cbr system when there is limited in C availability. In addition, we will study the role of an open reading frame upstream and overlapping with cbrA, called cbrX, and its involvement in transcriptional/translational regulation of CbrA. Methods: A deletion mutant of cbrA and cbrX (∆cbrXA) has been constructed (MPO494) in P. putida KT2442, and the phenotypic characterization of its ability to grow in a minimal medium using different C sources (succinate, citrate, histidine, glucose) has been evaluated. Also the transcriptional activation of three different targets of the Cbr regulatory system has been studied by analysis of the β-galactosidase activity of a transcriptional fusion to the promoter regions of crcZ, crcY, PP2810 [2]. Complementation of the mutant at the Tn7 integration site with the complete sequence cbrXA, and different constructs bearing cbrA or cbrX have also been constructed and their phenotypes analysed. Finally, a truncated form of CbrA expressed from heterologous Ptac promoter, which lacks 13 transmembrane domains, that is presumably not anchored to the inner membrane has also been constructed. Results: The ∆cbrXA deletion mutant MPO494 shows a longer lag phase when growing in succinate and glucose as C source, and even longer when growing on citrate medium, when compared to the wild-type strain KT2442. MPO494 is not able to use histidine as C source. Complementation of the MPO494 with cbrXA sequence fully recovers the wild-type phenotype. The activation of crcZ, crcY and PP2810 genes is 26 to 20 fold lower in a medium containing succinate or oxalacetate as C source in a mutant background compared to the KT2442, but it is fully complemented when the cbrXA sequence is supported in trans. The effects of cbrX on the CbrA expression/activity is currently being analysed.